A Rare Case of an Early Postoperative Obstructive Ileus in a Young Female Patient due to a Residual Trichobezoar Mass. (11th April 2016) - Christopoulos, P.; Ross-Thriepland, S.; McCarthy, H.; Day, C. S.; Sasi, W.
Abstract : Trichobezoar is a rare cause of small bowel obstruction, whereby a mass forms most commonly in the stomach and duodenum of young females, from ingestion of hair, a condition known as trichophagia. We present a case of recurrent small bowel obstruction due to a residual hair mass that was removed surgically in a young female patient who had a laparotomy and gastrotomy for removal of a large gastric trichobezoar just two weeks prior to the current admission. This case illustrates the importance of a thorough inspection of the whole bowel to ensure that no residual bezoars remain after surgery.